Implementation of Health Promoting School Management at SD Negeri 01 Pesantren, Pemalang Central Java : Toward a Whole-School Approach - Alafiyah, Cici Evianti; Kusumaningsih, Widya; Nurkolis, Nurkolis (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The quality of learning plays a crucial role in determining the overall standard of education. One of the key factors influencing learning quality is the presence of a healthy and comfortable school environment. SDN 01 Pesantren has been designated as a pilot school in the Healthy School Movement program, which aims to foster a safe, clean, and supportive environment to improve learning outcomes. This study focuses on the principal’s management strategies in implementing the program. A descriptive qualitative approach grounded in phenomenological research was employed, utilizing interviews, observations, and document analysis for data collection. The findings indicate that the implementation of the healthy school program was managed through four main stages: planning, organizing, actuating, and controlling. In the planning phase, the school conducted a needs assessment and set measurable goals related to student health and environmental hygiene. Organizing involved forming collaborative health teams, including teachers, health workers, and parents. Actuating was reflected in the implementation of regular health checks, hygiene education, and clean-up campaigns involving the school community. The controlling phase included ongoing monitoring of student health indicators, school cleanliness audits, and evaluation meetings. These core management functions enabled SDN 01 Pesantren to carry out the program effectively and efficiently. Furthermore, the results align with previous research by Herlina, who investigated the application of healthy school management at SMP Islam Cendekia Cianjur (SICC) Boarding School. Her findings underscore the critical role of management functions in organizing, directing, and optimizing resources to achieve organizational or programmatic goals effectively and efficiently.